Adverse Events for Overactive Bladder Medications From a Public Federal Database. Issue 7 (17th July 2022) - Sze, Christina; Drangsholt, Siri; Stoddard, Michelina D.; Singh, Zorawar; Sansone, Stephanie; Bhojani, Naeem; Zorn, Kevin; Elterman, Dean; Chughtai, Bilal
Abstract : Importance: Clinical data on the use of overactive bladder (OAB) medications are limited by the physician interpretation of adverse effects rather than those that are patient reported. Objective: The aim of the study was to evaluate the association between OAB medications and adverse drug events (ADEs) through the self-reporting U.S. Food and Drug Administration Adverse Event Report System database. Study Design: The U.S. Food and Drug Administration Adverse Event Report System (FAERS) database was queried from 2004 to 2019. Adverse drug events were recategorized. Disproportionality analysis was used to detect the risk signals for each OAB medication and ADEs. χ 2 values were calculated to assess the association between ADEs and dosage. Results: A total number of 14, 102 reports were identified. The most frequently reported OAB medications were mirabegron (35%), transdermal oxybutynin (27%), and solifenacin (25%). Neuropsychiatric (NP) ADEs were highest with tolterodine and fesoterodine usage (16% and 15.6%, respectively) and transdermal oxybutynin had the lowest (6.5%). Increasing the dose of tolterodine or fesoterodine was not associated with increased NP ADEs. Oxybutynin had the highest risk of affect/mood disorder, agitation, and balance/movement disorder; however, it had the lowest risk of headache/migraine compared with all OAB medications. Mirabegron compared with all other OAB medications had the lowest risk of affect/mood disorder and agitation; however, it had the highest risk of headache and migraines. Conclusions: The FAERS database not only is a repository of ADEs but also may represent evolving prescribing habits for OAB medications. Transdermal oxybutynin had the lowest NP ADEs and may be appropriate for selected individuals.